Research in Communication in Colombia seen from Web of Science - Arroyave-Cabrera, Jesús (2020)
Communication research in Colombia is already considered a consolidated field in the national context, but it is not in its international projection. International databases, in particular the Web of Science have become a widespread form of legitimation of knowledge in science at the Global Academy, but Colombian research on communication in these databases has hardly been studied. This article investigated how is the production and circulation of knowledge in one of the most widely used database, Web of Science. The results show that the research of authors linked to the Colombian academy went from a very low figure in the nineties, to a significant growth in 2008 and exponentially in 2015. The creation of the Emerging Source Citation Index database contributed greatly to this change. Implications for the production and appropriation of communication knowledge in Colombia are derived from this analysis.